2011
DOI: 10.1016/j.jvs.2011.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cerebral Embolisation in Asymptomatic and Recently Symptomatic Patients with TIA/Minor Stroke

Abstract: Objectives: Spontaneous embolisation (SE) detected using Transcranial Doppler (TCD) after a Transient Ischaemic Attack (TIA)/Minor stroke is an independent predictor of recurrent stroke. There are, however limited data on the differential prevalence of SE in the first few days/weeks after onset of symptoms.Method: 156 consecutive patients (symptomatic n ϭ 123, asymptomatic n ϭ 33) underwent Carotid Endarterectomy (CEA) during an 18 month period and had an accessible window permitting 30 min of preoperative TCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In the 2011 audit, Salem reported that 18/123 patients (15%) suffered recurrent symptoms in the (median) 3-day time period between transfer from the TIA clinic and undergoing CEA. 9 None, however, were strokes. In a second (2013) audit, Ali observed that 10/89 patients (11%) suffered recurrent neurological events (TIA ¼ 8;…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the 2011 audit, Salem reported that 18/123 patients (15%) suffered recurrent symptoms in the (median) 3-day time period between transfer from the TIA clinic and undergoing CEA. 9 None, however, were strokes. In a second (2013) audit, Ali observed that 10/89 patients (11%) suffered recurrent neurological events (TIA ¼ 8;…”
Section: Discussionmentioning
confidence: 98%
“…12 Similar data (regarding spontaneous embolization rates) were available from the two preceding audits in 2010 and 2011. 9,10 In addition, the time from flow restoration to removal of drapes was used as a surrogate for the delay to achieving haemostasis. In view of the temporal changes in patch type (and the effect/bias this might have had on haemostasis), three consecutive patient cohorts were analyzed: (i) January 1, 2011 to December31, 2011: polyester patch with regular aspirin þ 75 mg clopidogrel the night before surgery (n ¼ 96); (ii) January 1, 2012 to May 31, 2013: bovine pericardial patch with regular aspirin þ 75 mg clopidogrel the night before surgery (n ¼ 122); and (iii) August 17, 2013 to July 27, 2014 (the current audit): bovine pericardial patch with regular aspirin þ 75 mg clopidogrel starting once ICH was excluded in the TIA clinic (n ¼ 100).…”
Section: Post-operative Carementioning
confidence: 99%
See 1 more Smart Citation
“…15 The latest evidence suggests that CEA could also be performed during the hyper acute period without significantly increasing the operative risk in neurologically stable patients. 18,19,35 The operative risk remains high however for CEA performed in cases of neurological instability (associated brain hemorrhage, large volume cerebral infarctions with persistent disabling massive deficit, stroke-in-evolution). 19 For this reason, we decided to operate only on neurologically stable patients regardless of the time at which they reached stability.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, Harrison and Marshall showed that when CEA was performed within 4 weeks of the index TIA, 66% of patients had thrombus overlying their plaque compared with only 21% when CEA was performed thereafter. 10 Surgeons who have regularly been performing CEA within 7 days of symptom onset increasingly encounter grossly disrupted plaques with large amounts of overlying thrombus (Fig. 1), which is associated with higher rates of spontaneous embolization being detected on transcranial Doppler in the early time period after symptom onset (42% prevalence at < 7 days of symptom onset, 22% at 8e14 days, and 16% for > 14 days).…”
Section: Why Is the Early Stroke Risk So High?mentioning
confidence: 99%